A reliability generalization meta-analysis of Child Oral Impacts on Daily Performances (C - OIDP) questionnaire - Kalyana Chakravarthy Pentapati; Sravan Kumar Yeturu; Hanan Siddiq (Elsevier, 2020)
Aim: To evaluate the cumulative estimates of reliability and conduct reliability generalization meta-analysis of Cronbach's alpha for the Child Oral Impacts on Daily Performances (C-OIDP) questionnaire. Methodology: Systematic search of four databases from inception to November 30th, 2019 was performed. Studies that reported Cronbach alpha for the C-OIDP were included. Cronbach's alpha for each publication was used for the meta-analysis. I2 and Q statistics were calculated to assess heterogeneity. Meta-analysis was performed using a random-effects model to derive a pooled estimate of Cronbach's alpha. Results: Out of 944 publications, data extraction was done from 33 publications after exclusion. The age range among the included publication was from 6 to 19 years. Cronbach's alpha ranged from 0.53 to 0.9. Majority of the publications (n = 21) reported alpha above the benchmark (0.7 and above). Only two publications used condition-specific C-OIDP questionnaires. Twelve publications used self-administered child-OIDP questionnaires. Most of the studies were at a low risk of bias (n = 29). The cumulative alpha was higher in publications with a low ROB (α = 0.74) than a moderate ROB (α = 0.65) The cumulative alpha was 0.73 (SE = 0.02) with a high heterogeneity among the included publications (I2 = 99.28% and Q = 2048.68; P < 0.001). Conclusion: Overall, the RG estimate of Cronbach's alpha for C-OIDP was above the widely accepted benchmark.